Polymorph Identification and Crystal Structure Determination by a Combined Crystal Structure Prediction and Transmission Electron Microscopy Approach. Issue 24 (16th April 2013) - Eddleston, Mark D.; Hejczyk, Katarzyna E.; Bithell, Erica G.; Day, Graeme M.; Jones, William
Abstract Electron diffraction offers advantages over X‐ray based methods for crystal structure determination because it can be applied to sub‐micron sized crystallites, and picogram quantities of material. For molecular organic species, however, crystal structure determination with electron diffraction is hindered by rapid crystal deterioration in the electron beam, limiting the amount of diffraction data that can be collected, and by the effect of dynamical scattering on reflection intensities. Automated electron diffraction tomography provides one possible solution. We demonstrate here, however, an alternative approach in which a set of putative crystal structures of the compound of interest is generated by crystal structure prediction methods and electron diffraction is used to determine which of these putative structures is experimentally observed. This approach enables the advantages of electron diffraction to be exploited, while avoiding the need to obtain large amounts of diffraction data or accurate reflection intensities. We demonstrate the application of the methodology to the pharmaceutical compounds paracetamol, scyllo‐inositol and theophylline.